Hepatoprotective and Immunostimulatory Effect of Ganoderma, Andrographolide and Turmeric Against Aflatoxicosis in Broiler Chickens - AL-Zuhariy , Mushtaq T.B.; Hassan, Waleed H. (International Journal of Poultry Science, 2017)
Objective: The present study aimed to investigate the toxic effects of Aflatoxin (AF) B1 (AFB1) and evaluate the role of Ganoderma lucidum (GL), Andrographolide (AP) and Turmeric curcuma (CM) in reducing these toxic effects in broiler chickens. Material and methods: A total of 250 (Ross-308) one-day-old broiler chickens were randomly divided into 5 treatment groups (T1-T5) with 50 chicks per group. All groups except for T5 were fed diets that were contaminated with AFs and the groups were treated as follows: T1: Received 0.2% (2 g kg–1) GL as a feed additive. T2: Received 0.2% (2 g kg–1) AP as a feed additive. T3: Received 0.2% (2 g kg–1) CM as a feed additive. T4: Was a positive control (vaccinated but not treated). T5: Was a negative control (not vaccinated or treated). At ages 7, 15 and 25 days, all groups except T5 were vaccinated against Newcastle Disease (ND) (La Sota) and at 12 days, they were vaccinated against Infectious Bursal Disease (IBD) (intermediate D78 strain) (in drinking water). Twenty chicks from each group were challenged with a local virulent ND virus (NDV) isolate (ELD50 105) at 35 days. The AF content was 46.768 ppb in starter diets and 48.661 ppb in the final diet. Results: The GL-fed chicks produced the highest variable antibody titer (Abs), not significant (p